Infeksi Malaria dan Status Gizi Balita Pasca Gempa - Erlin Yustin Tatontos; Urip Urip (Bioscientist : Jurnal Ilmiah Biologi, 2023)
After the earthquake that occurred on Lombok Island during August 2018, malaria appeared again, especially in West Lombok Regency. The number of cases recorded was 753 people infected with malaria, including babies and pregnant women. Problems that arose after the earthquake on Lombok Island among babies and toddlers were malnutrition, including Insufficient Breast Milk (IBM) and Complementary Foods (CF) due to separation from their mothers. The aim of this research was to determine malaria infection and nutritional status of children under five in the earthquake-affected area in West Lombok Regency. The research method uses a qualitative approach. Data collection used was in-depth interviews, observation, and document study. Data analysis with the Epi info test. The results obtained were that the number of cases of malaria infection in the earthquake-affected areas in West Lombok Regency, especially the Penimbung Community Health Center, in 2018 was 753 cases and in 2019 there were 299 cases. Nutritional status in 2018 and 2019: 5,775 people with good nutrition: 710 people with poor nutrition, and 6 people with Low Birth Weight (LBW). The conclusion that can be drawn is that there is no relationship between post-earthquake malaria and the nutritional status of children under five.